PREVENTION AND TREATMENT OF POSTPARTUM HEMORRHAGE: A LITERATURE REVIEW - Yohana Rita Bitbit; Mardiana Ahmad; Isharyah Sunarno (Nurse and Health: Jurnal Keperawatan, 2022)
Background: The main cause of morbidity and maternal mortality is hemorrhage postpartum, with an increasing incidence around the world. Various risk factors for postpartum bleeding are expected to be an effective treatment by health professionals and have a role as advocates, collaborators, educators, service providers, and as researchers must have the latest knowledge in providing optimal and comprehensive care. Objectives: This study aimed to find out the prevention and treatment of hemorrhage postpartum. Design: This study design is a systematic review to search and review articles from database and the descriptive theory. Data Sources: Search scientific articles using the Mendeley application by entering the keywords "Postpartum, Hemorrhage, Prevention, and Treatment" with publication year 2019-2021, English, full text, and open access. Review Methods: The literature review method uses a narrative review to discuss postpartum hemorrhage, its prevention, and treatment. The inclusion criteria are the year of publication 2019-2021, international publications, articles in English, original articles, full text, and open access. Data were collected and a journal summary was made which included the name of the researcher, year of publication of the journal, research title, method, and a summary of the results or findings. Results: From 9 journals that meet the conclusion that active management of the third stage, administration of uterotonics and bimanual compression, is the initial treatment for the prevention and treatment of postpartum hemorrhage. Conclusion: In the prevention of risk factors for postpartum hemorrhage, it is recommended to carry out good active management of the third stage, use of uterotonic drugs according to the recommended dose, early initiation of breastfeeding, and increase the knowledge and skills of health workers.